Co-creation and co-destruction: A practice-theory based study of interactive value formation - Echeverri, Per; Skålén, Per (Marketing theory, 2011)
Drawing on an empirical study of public transport, this paper studies interactive value formation at the provider—customer interface, from a practice—theory perspective. In contrast to the bulk of previous research, it argues that interactive value formation is not only associated with value co-creation but also with value co-destruction. In addition, the paper also identifies five interaction value practices — informing, greeting, delivering, charging, and helping — and theorizes how interactive value formation takes place as well as how value is intersubjectively assessed by actors at the provider—customer interface. Furthermore, the paper also distinguishes between four types of interactive value formation praxis corresponding with four subject positions which practitioners step into when engaging in interactive value formation.